Johannes, R. E. Words of the Lagoon, Fishing and Marine Lore in the Palau District of Micronesia. Berkeley, Los Angeles y Londres: University of California Press, 1992. 245 p. fotos y dibujos - Devalle, Susana B. C (Estudios de Asia y África, 2004)
-